1996
DOI: 10.1111/j.1751-1097.1996.tb01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation of lndole‐3‐Acetic Acid and Inhibition of Growth in Avena sativa Seedlings by Plant‐Derived Photosensitizers*

Abstract: Abstract— A number of plant phototoxins, when supplemented with UVA (320–400 nm) radiation, are capable of sensitizing the decomposition of indole‐3‐acetic acid (IAA), as measured by release of 14CO2 from carboxyl‐labeled IAA. Alpha‐terthienyl (αT) and harmine caused significant rates of IAA decarboxylation at concentrations as low as 1 nM and were approximately 80% as effective as riboflavin and flavin mononucleotide. Partial inhibition by sodium azide indicates that the aT‐induced decarboxylation of IAA is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The activity of α -terthienyl was also tested in dark and light for C. reinhardti , as shown in the Figure S1 , where the result shows that α -terthienyl still retained activity in the darkness. Furthermore, Campbell [ 16 ] and Brennan [ 20 ] also reported the activity of α -terthienyl on plants in dark, and Gommers [ 21 ] reported that it had a high activity on nematodes. It does seem that α -terthienyl is capable of exerting toxic effects in the absence of light.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of α -terthienyl was also tested in dark and light for C. reinhardti , as shown in the Figure S1 , where the result shows that α -terthienyl still retained activity in the darkness. Furthermore, Campbell [ 16 ] and Brennan [ 20 ] also reported the activity of α -terthienyl on plants in dark, and Gommers [ 21 ] reported that it had a high activity on nematodes. It does seem that α -terthienyl is capable of exerting toxic effects in the absence of light.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it does seem that ␣T is capable of exerting toxic effects on both plants (4,6) and animals (7) in the absence of light. Thiarubrines, related UVA-absorbing compounds produced in the roots of some plants, show lightindependent fungal toxicity that is proposed to result from the reactivity of their 1,2-dithiin ring, possibly with a specific enzyme in the fungus (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the toxic effects of ␣T cannot be explained in terms of its normal photosensitizing properties. For example, the ␣T-induced inhibition of seedling growth noted above was significantly more pronounced in the presence of UVA, but was also clearly observable in the dark (approximately 30% inhibition with 10 M ␣T ϩ UVA versus 15% with ␣T alone) (6). Also, the germination and growth of several weed species are inhibited by ␣T concentrations in the range of 1-10 ppm in the absence of UVA treatment (4).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was shown to participate in the mechanism of colonization of alfalfa roots by Sinorhizobium meliloti (Yang et al, 2002), to promote induction of embryogenic callus in Zoysia japonica (Asano et al, 1996) and to protect auxin from oxidation (Brennan, 1996).…”
Section: Other Phenolic Compoundsmentioning
confidence: 99%